P8 Refractory thrombocytopenia in a patient with Systemic Lupus Erythematosus and secondary antiphospholipid syndrome. (23rd March 2020) - Torres, Rita; Gonçalves, Maria João; Gonçalves, Nuno; Manica, Santiago; Neto, Agna; Marona, José; Costa, Manuela; Pimentel-Santos, Fernando M; Branco, Jaime C
Abstract : Background: Thrombocytopenia is a frequent hematological manifestation in patients with systemic lupus erythematosus (SLE), usually treated with glucocorticoids, immunosuppressants (such as azathioprine and cyclophosphamide), intravenous immunoglobulin (IVIG) or splenectomy. Case report: A 44-year-old woman diagnosed with SLE and secondary antiphospholipid antibody syndrome was admitted in our hospital, in July 2018, presenting severe renal and haematological involvement. She underwent treatment with methylprednisolone, followed by prednisolone, and mycophenolate mofetil, with no response. In August 2018, the patient started haemodialysis, human immunoglobulin (transient response) and plasmapheresis due to evidence of secondary thrombotic microangiopathy. The refractory severe thrombocytopaenia and lupus nephritis, justify two cycles of rituximab - platelet count rising lasted for five months. Seven months later, the patient presented pancytopenia and due to high hemorrhagic risk, there was a switch from warfarin to LMWH (prophylactic dosing). One month later, anti-coagulation was suspended due to spontaneous intracranial bleeding. In August 2019, the patient had an ischemic stroke of the right occipital lobe, secondary to APS, under prednisolone and hydroxychloroquine, and with platelet count of 24.000/uL. Because of the bleeding risk, no anti-aggregation was instituted, and she started tacrolimus - the initial good response disappeared two weeks later. After consulting a rheumatology board, tacrolimus was kept and rituximab repeated, regardless of the hypogammaglobulinemia and no lymphocytes CD19+ count. Conclusion: We experienced a severe case of secondary thrombocytopenia, that was refractory to multiple therapeutic agents. A reasonable response was obtained under rituximab. Tacrolimus is kept due to the reported cases of late effect. Ischaemic stroke is a challenging condition in patients thrombocytopenic and further clinical guidance is warranted.